Participatory elaboration of Conduct Adjustment Agreements:: a socio-environmental reflexion opportunity? - Klunk, Luzia; Oliveira, Renato de; Turatti, Luciana (Sustainability in Debate, 2017)
The use of natural resources can lead to environmental conflicts, as it encompasses aspects inherent to its complexity. Additionally, there is a weak State dealing with those conflicts posing, thus, a need for public debate. The purpose of this article is to analyze the legal effects of environmental conflicts, identify ways to substitute unilateral deliberation for the participation in Conduct Adjustment Agreements (TACs) and to indicate if these agreements are creating an understanding of the environmental phenomena. A study in Public Civil Inquiries was carried out at the Public Prosecution Office in Lajeado, using TACs signed by individual persons from January, 2008 to January, 2014 by means of a bibliographical and documental research, and by conducting interviews. The conclusions led to the understanding that there is little participation in the drafting of TACs, and there was no increased knowledge about the environmental phenomena with those involved.